The magnitude of differences in perceived general health associated with educational level in the regions of Spain. Issue 5 (1st May 1999) - Regidor, E; Dominguez, V; Navarro, P; Rodriguez, C
Abstract : STUDY OBJECTIVE: To examine and compare the relation between inequalities in perceived general health and education in the 17 regions of Spain. DESIGN AND METHODS: Data were taken from the 1993 Spanish Health Interview Survey. For each region we calculated the magnitude of inequality in perceived general health in association with educational level by a measure of association or effect and by a relative index of inequality. Both measures are odds ratios and were estimated by logistic regression. The first is an odds ratio associated with one year less education, while the second represents the inequality in perceived general health between those at the bottom and those at the top of the educational hierarchy. MAIN RESULTS: The six regions with the highest relative indices of inequality also have the highest odds ratios associated with one year less education, and five of the six regions with the lowest relative indices of inequality have the lowest odds ratios associated with one year less education. Pearson's correlation coefficient between the odds ratio and the relative index of inequality is 0.94. CONCLUSIONS: Regional differences in levels of inequality in perceived general health are attributable exclusively to the effect of education on health and not to the distribution of the population among the different educational levels. It is not known why the magnitude of this effect of education on health varies from one area to another.